A Case Study of Organizational and Curricular Attributes for Interprofessional Education: A Model for Sustainable Curriculum Delivery - Azzam, Mohammad B.; Drynan, Donna; Fricke, Moni; Langlois, Sylvia; MacDonald, Laura; Vanier, Marie-Claude; Puvirajah, Anton (Journal of Research in Interprofessional Practice and Education)

(untitled) (Canadian Institute for Studies in Publishing Press (Simon Fraser University at Harbour Centre), 2023)
Background: In health and social care (HASC) professional education, interprofessional competencies are optimally developed by engaging in interprofessional education (IPE) activities that are delivered sustainably along a continuum. Ultimately, active engagement in IPE is meant to prepare future practitioners for interprofessional collaborative practice (IPCP), which leads to improved patient/client and community-oriented outcomes.Methods and Findings: This qualitative case study explores how four Canadian post-secondary institutions deliver IPE within their HASC professional education programmatic structures. Data were collected from institutional websites, publicly available IPE relevant records and documents, and interviews with coordinators and faculty/facilitators of IPE curriculum. Data were inductively analyzed to generate relevant themes, followed by a deductive analysis guided by the five accreditation standards domains identified in the Accreditation of Interprofessional Health Education (AIPHE) projects. Analyses of the data resulted in five attributes: 1) central administrative unit, 2) longitudinal and integrative program, 3) theoretically informed curriculum design, 4) student-centred pedagogy, and 5) patient/client-oriented approach.Conclusions: Using these attributes and guided by AIPHE’s accreditation standards domains, an organizational-curricular model for sustainable IPE is proposed, through which we assert that IPE reinforced through these organizational and curricular supports reflects successful programming, leading to patient/client-oriented outcomes.